Effect of achievement motivation and self-efficacy on general well-being among students at normal universities in Ningxia: the mediating role of time management - Dong, Jingyi; Che Hassan, Norlizah; Hassan, Aminuddin; Chen, Dan; Guo, Wei (MDPI AG, 2023)
General well-being is a positive evaluation of one’s mental health, which is an important topic in mental health. General well-being is fundamental to the positive development of young people. A thorough understanding of the factors that influence happiness have not yet been developed for students at normal universities in Ningxia Province in China. This study examined the mediation effects of time management on the relationship between achievement motivation, self-efficacy, and general well-being among students at normal universities in Ningxia Province in China. Using a random sampling, 163 participants (68 males and 95 females) completed the Achievement Motivation Scale (AMS), General Self-efficacy Scale (GSES), Time Management Questionnaire (TMQ) and General Well-being Scale (GWBS). Achievement motivation, self-efficacy, and time management were positively correlated with general well-being. The mediation effects of time management on the relationships between achievement motivation, self-efficacy, and general wellbeing (0.169 and 0.447) were demonstrated. These results add to the nuanced relationship between self-efficacy, achievement motivation, and general well-being. According to the Achievement Motivation Theory and the Self-efficacy Theory, this study reveals the role of achievement motivation, self-efficacy on general well-being and the mediating effect of time management in the relationship between achievement motivation, self-efficacy, and general well-being. According to the findings, the school can carry out a series of lectures and tutoring activities to enhance students’ achievement motivation, self-efficacy, time management, and general well-being.